Pengaruh Penerapan Digital Marketing Untuk Peningkatan Pendapatan UMKM Sekar Handycraft - Agung Triayudi; Mesran; Suginam; Joli Afriany; Fifto Nugroho (Forum Kerjasama Pendidikan Tinggi, 2023)
In today's era of digitalization, the implementation of effective marketing strategies becomes crucial for the growth of Small and Medium-sized Enterprises (SMEs). Sekar Handycraft, as an example of an SME in the handicraft sector, faces challenges in enhancing visibility and market access. This research utilizes a quantitative approach with a survey method involving data collection through questionnaires from Sekar Handycraft customers. Linear regression analysis is employed to measure the relationship between the implementation of digital marketing and income improvement. The research results indicate that the implementation of digital marketing has a positive and significant impact on the income improvement of Sekar Handycraft as an SME. These findings suggest that digital marketing strategies, including the utilization of social media, websites, and e-commerce platforms, can enhance product exposure and expand market reach for SMEs. In the context of global competition, adapting to digital marketing tools becomes a necessity for SMEs to remain relevant and sustainable. This research provides insights into the importance of digital transformation in SME development and offers guidance to similar businesses on optimizing the use of digital platforms to boost income. However, aspects such as technological access capability and understanding of digital marketing also need to be considered to fully realize the benefits of these strategies.